Barbarzyńcy w "Vita sancti Severini" - Dutka, Wojciech (Vox Patrum, 2003)
One of the major hagiographic sources of the Late Antiquity, Vita Sancti Severini, written by an abbey of the Lucullanum monastery, Eugippius, is also an excellent basis to explore the national and cultural contexts of living the Romans and the „barbarians" in the area of three Roman province: Noricum Ripense, Noricum Mediterraneum and Pannonia Maior in the sccond part of 5th century AD. However, the hagiographer identified 6 main names of „barbarian" tribes: the East Goths, the Herules, and the Thurings, Alemans, Rugians and Turkish Huns. Author characterized each of them comparing with the all historical details. The author also tried to analyze why the hagiographer had shown the Germanic tribes as a difficult neighbor than enemy? The religion context of these hagiographic tales also aimed to discover Germanie conquerors as so called „brothers" in Christianity. But most of the historians and philosophers of the Late Antiquity were able to think that co-operation with the Arian conquerors, was another unworkable idea. Eugippius was not. He tried to bridge the empty space of misunderstanding between the Romans and the Germanic people. Author considered the foliowing final reflection: it was possible that Eugippius could participate in the movement of cohabitation the Romans and East-Goths during the reign of Theodoric the Great. But author also tries to say that this is only a hypothesis.